The Influence of Mulching and GA3+Iron Mixture on Head Folding,Bitterness and Quality of Produced Seeds of Lettuce Lactuca sativa var. Longifolia cv. Marul. - Mahmood, Chinur H.; Abdel, Caser G. (Sulaimani Journal for Pure and Applied Sciences, 2015)
This study was carried out during the period between November, 2013 and August, 2014 to decrease unfolding, bitterness and tip burns through adopting a new screening method and to produce lettuce seeds and head yields of high qualities. Seeds and plants raised from them were treated with mixtures of [0 and 10 mg.l-1 GA3 + 25 mg.l-1 Fe, 10 mg.l-1 GA3 + 50 mg.l-1 Fe and 10 mg.l-1 GA3+ 75mg.l-1 Fe]. Plants grown on mulched and unmulched soils. Mulched soil plants displayed superiority over bare soil in terms: number of unfolded leaves, stem length and leaves number by 48.75, 110.85 and 22.23%, respectively. However, unmulched soil bypassed mulched soil in T.S.S. and dry matter percentages of folded leaves, unfolded leaves, stem and folded leaf base (23.96, 19.41, 30.59, 22.17, 18.52, 28.6, 18.54 and 27.24%, respectively). Lettuce grown on mulched soil revealed superiority over that grown on bare soil in N content of folded and unfolded leaves (23.1 and 68.75%, respectively), K content of folded leaves, stem and folded leaf base (57.85, 42.02 and 24.43%, respectively), Fe content of stem and folded leaf base (106.11 and 54.02 g.kg-1, respectively), Ca content of folded leaves, unfolded leaves, stem and folded leaf base (424.09, 235.96, 206.02 and 296.78%, respectively). 10 mg.l-1 GA3 + 75 mg.l-1 Fe displayed preponderance over untreated plants in head fresh weight (26.43%), head yield (26.16%), TSS (15.52%), branches number after chopping (92.9%), branch heights (66.98%) leaf number (30.82%), B content of folded leaves and stem (143.23 and 57.89%, respectively), N content of the folded leaf base (49.73%), K content of folded leaves (7.15%), Fe content of stem (152.14%) and Cu content of stem (39.54%). Lettuce plant treated by 10 mg.l-1 GA3 + 50 mg.l-1 Fe grown on mulched soil overwhelmed other dual interaction treatments as it showed the highest values in head fresh weight (821 g), head yield.m-2 (4.93 kg), weight of folded leaves (483.75 g), number of unfolded leaves (23.75) and weight of unfolded leaves (335 g).
Keywords: Mulching; GA3Iron Mixture; Lettuce seed